Heat Shock Protein 70 (Hsp70) Level is Lower in Premature Rupture of Membrane - Radam, Muhammad RA (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To prove whether the levels of Heat Shock Protein 70 (Hsp70) was lower in women experiencing premature rupture of membranes than in women with normal aterm pregnancy in order to explain occurrence of pregnancy premature rupture of membranes at termin biomolecular (Hsp70). Method: This was an observational research and the study design was a cross-sectional study. The number of all samples was 60 women, divided into 2 groups and each group contained 30 women. Independent variable: Heat Shock Protein 70 level, Dependent variable: Premature Rupture of Membrane. Data was analyzed by t test. Result: Based on maternal characteristic on both groups, the mean levels of Hsp70 in serum of pregnant women with PROM lower (0.36) compared to normal pregnant group (3.94) and this difference was statistically significant (p50%). Conclusion: Theme an levels of Hsp 70 in premature rupture of membranes obtained lower levels than in normal full-term pregnancy and this difference was statistically significant. [Indones J Obstet Gynecol 2014; 2: 69-75] Keywords: Heat Shock Protein 70, maternal stress, PROM